Revisión sistemática sobre la administración rutinaria de hierro durante el puerperio - Capurro , Haroldo; Lede , Roberto; Rosanova, María Teresa; Copertari, Pablo; Copertari, Pablo; Petrungaro, Virgilio (Revista Argentina de Salud Pública, 2010)
Revisión sistemática sobre la administración rutinaria de hierro durante el puerperio